2020
DOI: 10.1093/infdis/jiaa243
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide-Based Magnetic Chemiluminescence Enzyme Immunoassay for Serological Diagnosis of Coronavirus Disease 2019

Abstract: SARS-CoV-2, a novel ß-coronavirus, cause severe pneumonia and has spread throughout the globe rapidly. The disease associated with SARS-CoV-2 infection is named COVID-19. To date, real-time RT-PCR is the only test able to confirm this infection. However, the accuracy of RT-PCR depends on several factors; variations in these factors might significantly lower the sensitivity of detection. Here, we developed a peptide-based luminescent immunoassay that detected immunoglobulin G (IgG) and IgM. The assay cut-off va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 5 publications
2
133
0
Order By: Relevance
“…Recently, a peptide-based magnetic chemiluminescence enzyme immunoassay was developed for the diagnosis of COVID-19 [75]. The test has high throughput and can perform simultaneous clinical tests for other biomarkers, such as C-reactive protein (CRP), which should also be tracked in COVID-19 suspects [76].…”
Section: Immunoassays For Antibody To Virusmentioning
confidence: 99%
“…Recently, a peptide-based magnetic chemiluminescence enzyme immunoassay was developed for the diagnosis of COVID-19 [75]. The test has high throughput and can perform simultaneous clinical tests for other biomarkers, such as C-reactive protein (CRP), which should also be tracked in COVID-19 suspects [76].…”
Section: Immunoassays For Antibody To Virusmentioning
confidence: 99%
“…Chemiluminesence immuno-assay is one such an approach that has been popularly used in the detection of infectious diseases. Recent studies have demonstrated the application of this method for SARS-CoV-2 [199] , [200] , [201] . Cai et al [200] demonstrated a peptide-based magnetic chemiluminesence enzyme immuno-assay for detecting SARS-CoV-2 antibodies against ORF1a/b, N and S proteins.…”
Section: Rising Test Strategies For Covid-19 Diagnosismentioning
confidence: 99%
“…Although some studies confirm this trend, combining IgG and IgM signals gives even better signals (vide infra), especially that the shedding routes are multiple [ 178 ]. It is also possible to detect SARS-CoV-2 antibodies present in serum samples from people infected with other respiratory pathogens using a peptide that is attached to magnetic beads to act as the immunosorbent in a chemiluminescence enzyme immunoassay [ 193 ] with a similar magnitude of sensitivity (82.52%). In a similar way, Ashtari et al reported the use of hybrid magnetic NPs coated with amino-modified silica (ASMNPs) fabricated by water-in-oil microemulsion method for the improved recovery of target single-stranded DNA (ssDNA) macromolecules [ 194 ].…”
Section: Diagnostics and Biosensors For Covid-19mentioning
confidence: 99%